S100 Proteins, Cytokines, and Chemokines as Tear Biomarkers in Children with Juvenile Idiopathic Arthritis-associated Uveitis. (17th November 2021) - Angeles-Han, Sheila T.; Miraldi Utz, Virginia; Thornton, Sherry; Schulert, Grant; Rodriguez-Smith, Jackeline; Kauffman, Adam; Sproles, Alyssa; Mwase, Najima; Hennard, Theresa; Grom, Alexei; Altaye, Mekibib; Holland, Gary N.
ABSTRACT: Purpose : Biomarkers for juvenile idiopathic arthritis-associated uveitis (JIA-U) are needed. We aimed to measure inflammatory biomarkers in tears as a noninvasive method to identify biomarkers of uveitis activity. Methods : Tears were collected from children with JIA-U (n = 20) and pediatric controls (n = 20) using Schirmer strips. S100A8, A9, A12, IL-18, IL-8, IP-10, MCP-1, RANTES, and sICAM-1 were measured by ELISA and Luminex assays. Levels of biomarkers were compared between children with JIA-U and controls, and active and inactive JIA-U. Results : IL-8, sICAM-1, and S100A12 levels were similar between JIA-U and controls, but differed by activity. Active JIA-U had significantly increased S100A12 compared to inactive JIA-U (mean 27, 722.5 pg/ML (SE 1.3) vs. 5, 937.2 (1.3), p = .002), IL-8 (73.5 [1.2] vs. 36.2 [1.2], p = .009), and sICAM-1 (15, 822.7 [1.2) vs. 8, 778.0 [1.6], p = .024). Conclusion : We detected inflammatory biomarkers noninvasively in tears of children with JIA-U. IL-8, sICAM-1, and S100A12 are potential biomarkers for uveitis activity.